PROFESSIONAL QUALITY OF LIFE NURSING DOES NOT IMPROVE DIRECTLY TO QUALITY OF NURSING SERVICES IN EMERGENCY DEPARTEMENT SIDOARJO REGIONAL HOSPITAL - Hani Riska (UPT Penerbitan Universitas Jember, 2017)
Background: Nurses are the largest component of health care. Emergency Departement nurses must provide excellent service and quality so that the achievement of Compassion satisfaction, but the nurses must also deal with the conditions that cause a stressor for him so that appears Compassion Fatigue. The charges charged to the nurse create a separate stressor that can cause Burnout. This study aims to determine the relationship of professional quality of life with nursing service quality nurses ED Sidoarjo regional hospital. Methods: The design of this study used observational analytics with crossectional approach. Sampling approach using simple random sampling with a sample as much as 82 respondents consist of 41 nurses ED Sidoarjo regional hospital and 41 patients. Data analysis used spearman test. Results: The results showed that all respondents (100%) had high compassion satisfaction, 33 respondents (80.5%) experienced average burnout. and respondents (30.6%) experienced compassion fatigue on average. 23 respondents (56.1%) assessed the quality of good nursing service. Result of statistical test between compassion fatigue with quality of nursing service got p-value 0,028 (p> 0,05) and correlation coefficient (r) = 0,861. This means that there are a significant influence and positive correlation between the two. Test statistic between burnout with quality of nursing service got p-value 0,998 (p> 0,05) and correlation coefficient (r) = 0,000. This means there is no influence and also the correlation between the two. The correlation test between compassion satisfaction and nursing service quality cannot be done because all respondents have high compassion satisfaction. Conclusion: Professionalism is a reality that is expected by all parties working in the world of health services. Many obstacles to be able to realize the ideal conditions in an effort to realize the working climate. Keywords: Compassion Satisfaction, Compassion Fatigue, Burnout, Quality of Nursing